Notary Role in Making Using Standard Contract Technology Information in The Framework of Legal Protection of Small and Medium Enterprises (SMEs) - Moch. Asep Rusmana; Bambang Rudi Hartoko; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The purpose of this research is; (1) to analyze the role of the notary in contract manufacturing standards using technology information in a business transaction that is carried out by SMEs, and (2) to analyze the obstacles and solutions contract manufacturing standards using technology information in providing legal protection to SMEs. Researchers use various types of data in the study, such as; (1) primary data, (2) secondary data, and (3) the data tertiary. The three types of data must be mutually supportive and have conformity with one another so that the results of this study can be justified scientifically.The conclusion of this study, namely; (1) business contracts are usually carried out by SMEs in general do not engage the services of a notary. Form of the contract was generally not made in the format of a standard contract. In general, SMEs also do not use technology information in their business transactions. Only a small portion of SMEs that have used the services of a notary and technology information in conducting business transactions, (2) while the main obstacles SMEs have not been optimally use the services of a notary in the transaction business was due to cost factors (notary) who felt still quite burdensome, attributed to the relatively small volume of the SMEs business.Keywords; Notary; Standard Contracts; Technology Information; Legal Protection and SMEs.